(untitled) (Bioagro, 2020)
The two-spotted spider mite, Tetranychus urticae Koch, is considered the main pest to strawberry crop worldwide. Our objective was to study the life history, fecundity and longevity parameters of the on detached leaves of two strawberry cultivars (Festival and San Andreas) under laboratory conditions. Total developmental time (egg-adult) showed to be shorter (14.0 %) when mites were reared on ‘Festival’ than on ‘San Andreas’, although higher sex ratio was observed on the latter. Similarly, longevity, oviposition and post-oviposition periods in T. urticae females were significantly higher on ‘San Andreas’, being 28.9, 40.0 and 48.7 % higher as compared to ‘Festival’. Conversely, no cultivar effect on daily oviposition rate or total number of eggs/female was detected. Based on the biological parameters of T. urticae here in, ‘San Andreas’ showed greater susceptibility to damages inflicted by this mite.